Sobre a dor do existir : a configuração da melancolia em poemas românticos brasileiros - Picoli, Gilmárcia da Silva (2019)
This work aims to analyze melancholia, especially that which is present in poems of Brazilian Romanticism, by the poets Francisco Otaviano de Almeida Rosa, Manuel Antônio Álvares de Azevedo, Luís José Junqueira Freire, Laurindo Rabelo and Aureliano Lessa. In the search for a conception of melancholia and for analysis under this focus, the contributions of the authors Sigmund Freud, Julia Kristeva and Jean Starobinski were used to recognize how melancholy is configured in the chosen poems. From the theoretical study and analysis of the poems, the configuration of melancholy was constituted in three subthemes: death drive, sorrow of existence and propulsion to writing. In each poem was observed one or more of these sub-themes, which provided us the understanding of how the melancholia is configured in poetry. The organization of the work follows the order of a panorama of melancholia, its connection with Romanticism, and the analysis of poems.